The Correlation Between Bullous Concha Volume and Type of Nasal Septal Deviation with Lund-Mackay CT Score in Chronic Rhinosinusitis: The Correlation Between Bullous Concha Volume and Type of Nasal Septal Deviation with Lund-Mackay CT Score in Chronic Rhinosinusitis - Monica Cherlady Anastasia; Anna Mailasari Kusuma Dewi; Farah Hendara Ningrum (RSUP Dr. Kariadi, 2022)
BACKGROUND: Chronic rhinosinusitis is inflammation of the mucoperiosteum lining of the nose and paranasal sinuses for more than 12 weeks. Computed Tomography (CT scan) of the paranasal sinuses is the gold standard for diagnosing chronic rhinosinusitis. Nasal septal deviation and bullous concha are anatomical variation that often found in CT scan of chronic rhinosinusitis patients. The severity of chronic rhinosinusitis can be evaluated with Lund Mackay CT score. AIM: To analyse the correlation between bullous concha volume and type of nasal septum deviation with Lund-Mackay CT Score in chronic rhinosinusitis METHOD: This was an observational study with a cross sectional design. This study was conducted from March-May 2019. Subjects were CRS patients whom underwent paranasal sinuses CT scan in Dr. Kariadi Hospital Semarang whom met the criteria. The inclusion criteria were chronic rhinosinusitis patients more than 17 years old with deviated nasal septum and conchae bullosa. RESULT: There were 50 CRS patients, the age average is 18 – 67 years. The mean volume of the bullous concha was 0.534 cm3. The highest deviation of the nasal septum is to the right (53.2%) and the highest total Lund-Mackay CT Score was 4 (56%). The correlation between septal type and bullous concha volume with Lund-Mackay CT Score CONCLUSION: Lund Mackay CT score didn't correlate with septal type and bullous concha volume. KEYWORDS: Bullous Concha, Chronic Rhinosinusitis, Lund Mackay CT score, Nasal Septum Deviation